Implementasi Akuntansi Pertanggungjawaban Sosial dan Lingkungan dalam Meningkatkan Keberlanjutan Perusahaan - Siti Nurkhasanah; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the era of globalization, companies are required to not only focus on financial profits, but also to contribute to social welfare and environmental preservation. The application of social and environmental responsibility accounting is important in measuring, reporting and managing the impacts caused by company activities. Even though there are obstacles, such as a lack of management understanding and high implementation costs, companies that successfully implement this accounting can improve their image, customer loyalty and long-term financial performance. Integration with measurable and transparent Corporate Social Responsibility (CSR) programs further strengthens the company's contribution to sustainability. The use of global standards such as the Global Reporting Initiative (GRI) can facilitate more effective reporting, enabling companies to face sustainability challenges more adaptively, responsibly and competitively. The application of social and environmental accounting not only fulfills regulatory obligations, but is also part of a business strategy that supports company sustainability at local and global levels.